IDENTIFIKASI POTENSI SOSIAL BUDAYA DAN EKONOMI DI DESA KAYU AMBON KECAMATAN LEMBANG, KABUPATEN BANDUNG - Faida Normawati (Sosio Informa, 2005)
(Socio-cultural and Economic Potential Identification in Kayu Ambon Village, Lembang Subdistrict, Bandung District) - The Community's aspiration have valuable contribution to development. Exploration of community's potentia l is needed to support the empowerment effort, especially for pluralistic community. In addition, the various culture, environment and local values also should be considera ted. The community's po tential will become social capital that enforcing the economic development and prompted by linking social capital. Kayu Ambon Village located in Lembang Sub District, Bandung as trantition area with various social culture and economic potential. However, its have not been used to strengthen integrative social economic development.